2023
DOI: 10.3389/fgene.2023.1193944
|View full text |Cite
|
Sign up to set email alerts
|

A novel disulfidptosis-associated expression pattern in breast cancer based on machine learning

Abstract: Background: Breast cancer (BC), the leading cause of cancer-related deaths among women, remains a serious threat to human health worldwide. The biological function and prognostic value of disulfidptosis as a novel strategy for BC treatment via induction of cell death remain unknown.Methods: Gene mutations and copy number variations (CNVs) in 10 disulfidptosis genes were evaluated. Differential expression, prognostic, and univariate Cox analyses were then performed for 10 genes, and BC-specific disulfidptosis-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Disulfidptosis is closely related to tumor progression, and studies have found that disulfidptosis plays an important role in disease progression and prognosis in bladder, lung, breast, and cervical cancer [ [38] , [39] , [40] , [41] , [42] ]. Studies have confirmed that SLC7A11, SLC3A2, RPN1, NCKAP1, NDUFS1, NDUFA11, OXSM, NUBPL, and LRPPRC greatly contribute to the process of disulfidptosis, and interfering with these genes can effectively inhibit the progression of disulfidptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Disulfidptosis is closely related to tumor progression, and studies have found that disulfidptosis plays an important role in disease progression and prognosis in bladder, lung, breast, and cervical cancer [ [38] , [39] , [40] , [41] , [42] ]. Studies have confirmed that SLC7A11, SLC3A2, RPN1, NCKAP1, NDUFS1, NDUFA11, OXSM, NUBPL, and LRPPRC greatly contribute to the process of disulfidptosis, and interfering with these genes can effectively inhibit the progression of disulfidptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al employed the Least Absolute Shrinkage and Selection Operator (LASSO) regression algorithm to construct a prognostic model based on differentially expressed genes (DEGs). The model’s predictive accuracy and sensitivity were validated through prognostic analysis and receiver operating characteristic curve analysis ( Wang Z et al, 2023 ). These algorithms can differentiate between cancerous and non-cancerous samples, classify cancer subtypes, and predict treatment outcomes.…”
Section: Advanced Strategies and Technologies In Exosome-based Cancer...mentioning
confidence: 99%
“…Wang and colleagues also discovered three disulfidptosis-related genes, DNUFS1, LRPPRC, and SLC7A11, with differential expression and prognostic values. These findings offer important insights into predicting the prognosis of breast cancer patients [ 35 ].…”
Section: Disulfidptosis and Diseasementioning
confidence: 99%
“…Lung Cancer: G6PD [32]; OGFRP1 [33] Reproductive System Breast Cancer: CD80, CD276 [34]; DNUFS1, LRPPRC, SLC7A11 [35] Neurodeenerative diseases MYH9, IQGAP1, ACTN4, DSTN, ACTB, MYL6, GYS1 [45] Metabolic diseases TRXR1, NFATC1 [46]…”
Section: Respiratory Systemmentioning
confidence: 99%